A study on the ecology and economic impact of major invasive weed species of coconut homesteads of Nattika, India - Abhilash, ES; Parayil, Sheeja P; Sathian, Brijesh; Raju, AR; Bilal, NA; Salih, Kafsa Bind (Asia Pacific Journal of Environment Ecology and Sustainable Development, 2014)
Out of the 4 alien invasive species three are of high risk namely Mikania micrantha, Chromolaena odorata and Mimosa diplotricha. Lantana camara is found to be medium risk. The farmers spent a considerable amount of money nearly Rs 4800 per year for one acre land pertaining to mechanical weeding of invasive species. The herbicide is widely used by farmers to control the weeds are capable to cause various health problems including genetic aberration. So an effective and comprehensive weed management strategy have to be developed in the country to combat the threats of IAS in agriculture fields. DOI: http://dx.doi.org/10.3126/apjeesd.v1i1.9509 Asia Pacific Journal of Environment Ecology and Sustainable Development 2013; 1: 32-35